Dietary Isothiocyanate-induced Apoptosis via Thiol Modification of DNA Topoisomerase IIα - Lin, Ren-Kuo (American Society for Biochemistry and Molecular Biology, 2011)
Studies in animal models have indicated that dietary isothiocyanates (ITCs) exhibit cancer preventive activities through carcinogen detoxification-dependent and -independent mechanisms. The carcinogen detoxification-independent mechanism of cancer prevention by ITCs has been attributed at least in part to their ability to induce apoptosis of transformed (initiated) cells (e.g. through suppression of IκB kinase and nuclear factor κB as well as other proposed mechanisms). In the current studies we show that ITC-induced apoptosis of oncogene-transformed cells involves thiol modification of DNA topoisomerase II (Top2) based on the following observations. 1) siRNA-mediated knockdown of Top2α in both SV40-transformed MEFs and Ras-transformed human mammary epithelial MCF-10A cells resulted in reduced ITC sensitivity. 2) ITCs, like some anticancer drugs and cancer-preventive dietary components, were shown to induce reversible Top2α cleavage complexes in vitro. 3) ITC-induced Top2α cleavage complexes were abolished by co-incubation with excess glutathione. In addition, proteomic analysis revealed that several cysteine residues on human Top2α were covalently modified by benzyl-ITC, suggesting that ITC-induced Top2α cleavage complexes may involve cysteine modification. Interestingly, consistent with the thiol modification mechanism for Top2α cleavage complex induction, the thiol-reactive selenocysteine, but not the non-thiol-reactive selenomethionine, was shown to induce Top2α cleavage complexes. In the aggregate, our results suggest that thiol modification of Top2α may contribute to apoptosis induction in transformed cells by ITCs.